Community paediatricians' counseling patterns and knowledge of recommendations relating to child restraint use in motor vehicles. Issue 2 (5th April 2004) - Rothenstein, J; Howard, A; Parkin, P; Khambalia, A; Macarthur, C
Abstract : Background: Road traffic injury is the leading cause of death among Canadian children and youth. Transport Canada recommends four types of child restraint depending on the size of the child, and recent studies have demonstrated the effectiveness of recommended restraint use. Objectives: To determine community paediatricians' knowledge of Transport Canada recommendations for child restraint use in vehicles, and to examine paediatricians' counseling patterns in relation to child passenger safety. Methods: A mailed questionnaire survey of all community paediatricians affiliated with the Hospital for Sick Children, Toronto was conducted. A 16 item questionnaire gathered information on knowledge of Transport Canada recommendations for child restraint use, general counseling patterns in relation to child passenger safety, and demographic information. Results: In total, 60 community paediatricians in active practice were identified. Of these, 48 (80%) responded to the mailed questionnaire. Almost all paediatricians (92%) correctly identified the recommended weight for transition to a forward-facing car seat, whereas fewer paediatricians (63%) correctly identified the recommended weight for transition to a booster seat from a forward-facing car seat, and only one third of paediatricians correctly identified the recommended weight for transition from a booster seat to a seat belt. Conclusion: Community paediatricians' knowledge of Transport Canada recommendations for child restraint use in vehicles is incomplete. There is a need for such recommendations to be better disseminated to paediatricians and parents so that information on child restraint use is delivered in a clear and consistent manner.